Seeing Inversnaid: Gerard Manley Hopkins, "Inversnaid," and the Ecological Eye. - Flint, Kate (Victorian Poetry)
The article focuses on the poem "Inversnaid" by Gerard Manley Hopkins and investigates how his habits of seeing and his background as a sketcher influenced his observations of nature. It talks about how Hopkins' attention to detail and effort in capturing the invisible spirit of the natural world were shaped by John Ruskin. Additionally, it considers the connection between Hopkins' poem's appeal for ecological awareness and modern visual art that highlights the vulnerability of the environment.